Synthesis and structure of an aryltellurenium(II) cation; [4-tert-butyl-2,6-bis(1-pentyl-1H-benzimidazol-2-yl-κN3)phenyl-κC1]tellurium(II) (1,4-dioxane)triiodidomercurate(II) - Varsha Rani; Harkesh B. Singh; Ray J. Butcher (Acta Crystallographica Section E: Crystallographic Communications, 2018)
In the title salt, (C34H41N4Te)[HgI3(C4H8O2)], the aryltellurenium [C34H41N4Te]+ cations and [HgI3(dioxane)]− anions are linked by a short interaction between the Te atom and one of the I-atom donors of the anion, as well as through weak C—H...I interactions. The geometry around the Te atom is T-shaped with the coordination comprising a C atom of the central aromatic ring and two N atom donors of the benzimidazolyl moiety. The Te—N bond lengths are almost equal [2.232 (3) and 2.244 (3) Å], while the Te—C bond length is 2.071 (4) Å. The N—Te—N bond angle is 150.68 (11)°. The HgII atom of the anion is coordinated by iodide ions from three sides and the fourth coordination site is occupied by an O atom of the solvent molecule (dioxane). Thus, it attains a trigonal–pyrimidal geometry, with O—Hg—I angles ranging of 90.76 (8) and 96.76 (7)° and I—Hg—I angles ranging from 112.41 (1) to 125.10 (1)°. The cations and anions are involved in numerous weak π–π stacking interactions involving both the central phenyl ring and two inversion-related benzimidazole moieties, which propagate in the a-axis direction. In addition, there are numerous C—H...I interactions between the cations and anions, which link them into a complex three-dimensional array.